Synthesis and cytotoxic activity of tri-acyl ester derivatives of uridine in breast cancer cells (2016)
ABSTRACT: Synthesize tri-acyl ester derivatives of uridine, and evaluate its cytotoxicity against breast cancer cells line. Methods: The tri-esterified uridine derivatives were obtained through Steglich esterification reaction by fatty and aromatic acids, and with acetic anhydride. An acetonide derivative from uridine was prepared with acid catalysis. Compounds were characterized by NMR spectroscopy (1H NMR and 13C NMR), and mass spectrometry. Derivatives were assessed in chinese hamster ovary (CHO-K1) and human breast cancer (MCF-7) cell lines. Results: Five tri-acyl ester derivatives of uridine were obtained one acetic acid, three fatty acids (myristic acid, stearic acid and oleic acid) with an aromatic acid. The uridine per-acetylated and uridine acetonide were obtained in high yields, however, the tri-acyl ester derivatives of uridine with fatty and aromatic acids were obtained in moderate and low yields, respectively. The acetonide and compounds 2 and 3 exhibited a cell viability inhibition significant on both cell lines to the higher concentration. Conclusions: Esterification method with coupling agents allowed obtained tri-acyl ester uridine derivatives with aliphatic and aromatic acids. However, significant cytotoxic activity (p<0.05) for uridine and its derivatives was not observed.